Gender dimensions of farming practices in root and tuber crops and proposed gender and social considerations for interventions. Technical report. - Kawarazuka, Nozomi; Prain, Gordon (International Potato Center, 2018)
This report documents those detailed gender dimensions of RTC farming practices, showing how differently men and women engage in them, and it also provides a critical analysis of the gender considerations required for interventions. The report also presents the tentative action plans discussed during the gender training held in December 2017. Based on this documented information, we are going to propose gender-responsive support for proposed activities for both men and women farmers. The context-specific gender constraints and challenges written in this report will be shared with partner organisations and carefully addressed in each case.